The Design and Implementation of a Custom Platform for the Experimental Tuning of a Quadcopter Controller † - Waliszkiewicz, Michał (Sensors (Basel), 2020)
This paper describes the development process of the quadcopter-based unmanned flying platform, designed for testing and experimentation purposes. The project features custom-made hardware, which includes the prototype quadcopter frame and the flight controller, and software solutions, such as control loop setup. The article specifies the controller tuning used for the initialization of the flight stabilization system and presents the final results of the quadcopter performance evaluation.